A docência compartilhada: um olhar para a ação de professores dos anos iniciais do ensino fundamental e sua relação com o trabalho coletivo - Mazer, Inês Maria Silva Barros (Universidade Federal de São Carlos, 2024)
The present work was inspired by the Historical-Cultural theory and its general objective is to understand how the development of Shared Teaching occurs in the "Todos Juntos" Project and its relationship with Collective Work. To this end, the main question of this research is: "how can the development of pedagogical actions in Shared Teaching be related to Collective Work?". As specific objectives, we seek to identify the constituent characteristics of Shared Teaching and compare them with the elements of Collective Work. The object of study, therefore, is collective work in shared teaching. According to Hochnadel and Conte (2019), Shared Teaching consists of a shared action between two teachers in the classroom. Collective Work, for Makarenko (1977), occurs through the development of coordinated and organized actions with responsibility for the common benefit. In this sense, the collective is understood as a living organism of a society. In addition to these concepts, "dialogue" in this research is understood as in the Freirean perspective, as the force that drives critical and problematizing thinking, together with what Bohm (2005) establishes about the purpose of dialogue in going through the thought process to change the way it happens collectively. In relation to the instrument for constructing information, the Focus Group technique was used as a vehicle that provided opportunities for discussions relevant to the subjects studied here. This technique, in qualitative research, allowed group analysis, considering the group of participants, making it possible to obtain information on the proposed topic. The results of this research show that there are movements in the development of pedagogical actions in Shared Teaching that can lead to collective teaching work, although we conclude that we were unable to determine full support of the collective work in the "Todos Juntos" project, due to its duration. duration and other limitations such as the subjects, their activities and material conditions. Thus, after completing this research, we considered the construction of an educational product that would bring the relationships established between the characteristics of Shared Teaching and the elements of Collective Work with the aim of explaining a path for the construction of collective teaching work. This product is intended for everyone interested in the topic, especially teachers and other professionals who consider humanization as the key to their actions and propose to join efforts to build the collective as the strength, union and transformation necessary for education.

El presente trabajo se inspiró en la teoría Histórico-Cultural y tiene como objetivo general comprender cómo se da el desarrollo de la Enseñanza Compartida en el Proyecto "Todos Juntos" y su relación con el Trabajo Colectivo. Para ello, la pregunta principal de esta investigación es: “¿cómo se puede relacionar el desarrollo de acciones pedagógicas en la Enseñanza Compartida con el Trabajo Colectivo?”. Como objetivos específicos buscamos identificar las características constitutivas de la Enseñanza Compartida y compararlas con los elementos del Trabajo Colectivo. El objeto de estudio, por tanto, es el trabajo colectivo en la enseñanza compartida. Según Hochnadel y Conte (2019), la Enseñanza Compartida consiste en una acción compartida entre dos docentes en el aula. El Trabajo Colectivo, para Makarenko (1977), se da mediante el desarrollo de acciones coordinadas y organizadas con responsabilidad por el beneficio común. En este sentido, se entiende al colectivo como un organismo vivo de una sociedad. Además de estos conceptos, el “diálogo” en esta investigación se entiende desde la perspectiva freireana, como la fuerza que impulsa el pensamiento crítico y problematizador, junto con lo que Bohm (2005) establece sobre el propósito del diálogo al atravesar el proceso de pensamiento para cambiar la forma en que sucede colectivamente. En relación al instrumento de construcción de información, se utilizó la técnica del Focus Group como vehículo que brindó espacios para discusiones relevantes a los temas aquí estudiados. Esta técnica, en la investigación cualitativa, permitió el análisis grupal, considerando el conjunto de participantes, posibilitando obtener información sobre el tema propuesto. Los resultados de esta investigación muestran que existen movimientos en el desarrollo de acciones pedagógicas en Enseñanza Compartida que pueden derivar en un trabajo docente colectivo, aunque concluimos que no pudimos determinar un apoyo total al trabajo colectivo en el proyecto "Todos Juntos". por su duración y otras limitaciones como las materias, sus actividades y condiciones materiales. Así, luego de culminar esta investigación, nos planteamos la construcción de un producto educativo que traería las relaciones establecidas entre las características de la Enseñanza Compartida y los elementos del Trabajo Colectivo con el objetivo de explicar un camino para la construcción del trabajo docente colectivo. Este producto está dirigido a todos los interesados ​​en el tema, especialmente a docentes y otros profesionales que consideran la humanización como clave de su accionar y se proponen sumar esfuerzos para construir lo colectivo como fuerza, unión y transformación necesaria para la educación.
Shared teaching: a look at the actions of teachers in the early years of elementary school and their relationship with collective work
Enseñanza compartida: una mirada al accionar de los docentes en los primeros años de la educación primaria y su relación con el trabajo colectivo
Keywords: Docência compartilhada; Trabalho coletivo; Coletividade; Ensino fundamental; CIENCIAS HUMANAS::EDUCACAO